2007
DOI: 10.1143/jjap.46.342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sapphire Substrate Preparation on ZnO Epitaxial Growth by Atmospheric-Pressure Metal Organic Chemical Vapor Deposition

Abstract: One-dimensional Thue-Morse (ThMo) lattices are examples of self-similar structures that exhibit bandgap phenomena. ThMo multilayers may also possess fractal photonic bandgaps that give rise to large omnidirectional reflectance and light-emission enhancement effects. Two-dimensional (2D) ThMo aperiodic quasicrystals possess interesting properties for photonic applications too. Here we demonstrate the experimental fabrication of large area 2D ThMo lattices into polymeric substrates at nanometre scale by electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
1
9
1
Order By: Relevance
“…This domain aligns the [100] directions for both ZnO and Al 2 O 3 and has been observed in other ALD studies . For ZnO deposition at higher temperatures, other rotational domains have been observed, mainly one rotated around the [001] axis by ±30°, with respect to this one. The coincidence superstructure for T 1 shown in Figure a exhibits 6-fold symmetry. Indeed, the open white squares in the (100) and (101)-pole figures (Figures d and f) are consistent with this symmetry.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This domain aligns the [100] directions for both ZnO and Al 2 O 3 and has been observed in other ALD studies . For ZnO deposition at higher temperatures, other rotational domains have been observed, mainly one rotated around the [001] axis by ±30°, with respect to this one. The coincidence superstructure for T 1 shown in Figure a exhibits 6-fold symmetry. Indeed, the open white squares in the (100) and (101)-pole figures (Figures d and f) are consistent with this symmetry.…”
Section: Discussionsupporting
confidence: 79%
“…These ZnO grains fulfill the following epitaxial relationship: (001) ZnO∥(001) Al 2 O 3 and [100] ZnO∥[100] Al 2 O 3 (Figure a). While others have also found (001) domains with an in-plane rotation of 30°, with respect to these, a significant population of such domains were not observed here, since these would lead to additional (unobserved) reflections in the (101) pole figure.…”
Section: Resultsmentioning
confidence: 48%
“…For epitaxial growth of ZnO layers on sapphire substrate, rotational domains are a frequently reported problem. Therefore, we performed EBSD measurements on the sample grown for 300 min, shown in Figure . We were scanning an area of about 400 × 300 μm 2 in order to get a statistically significant result.…”
Section: Resultsmentioning
confidence: 99%
“…As pointed out above, the epitaxial in-plane relationship between ZnO and Al 2 O 3 depends on the relative alignment of ZnO to the O-sublattice of Al 2 O 3 . In recent publications [80,81], it has been demonstrated that a substrate annealing step at elevated temperatures prior to deposition leads to an oxygen-terminated surface, improving both the quality of the substrate and the epitaxial ZnO thin film. We studied this effect and found a significant improvement of the structural quality after annealing the substrate at T sub = 850 • C for 1 h in a pure O 2 atmosphere of 10 −3 mbar.…”
Section: Laser Fluencementioning
confidence: 99%